The Effect of Capital Adequacy Ratio on the Ratio of the Bank Reserves Accepted in the Tehran Stock Exchange - Taherinia, Masoud; Baqeri, Alirahm (International Journal of Economics and Financial Issues, 2018)
This research aimed to assess the effect of capital adequacy ratio on the ratio of the bank reserves accepted in the Tehran Stock Exchange also it was based on the Kashyap and Stein pattern (2004) and modified variables of Levintal (2005) research. Required data from the statistical population including 16 Iranian exchange banks has been achieved for a five year period from 2009 to 2013. The results of the research that indicated a direct relationship between capital adequacy ratio and bank reserves as an absorption rate of different deposits of customers in banks were considered as dependent variable. In addition, the interpretation of control variables slope in estimated relationship showed that there was an inverse relationship between rate of granted facilities and the size of bank with bank reserves; also there was a direct relationship between growth opportunities and profit volatility. Student t test for estimated coefficients and Fisher test for total estimated relationship supported the ability to generalize relationships between variables at 95% level. The coefficient of determination showed that between %83.5 to %87/5 changes between independent and control variables with bank reserves through expressed estimated relationship and estimated relationship between variables has had a fairly complete explanatory power. Keywords: Bank reserves, Capital adequacy, Facilities, The size of bank, Growth opportunity, Profit volatility JEL Classifications: G21, G3